2006
DOI: 10.1093/annhyg/mel058
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Self-Assessment of Exposure to Solvents Among Shoe Repair Men

Abstract: Self-assessment of exposure (SAE) refers to any exposure assessment methodology wherein the worker takes an active role in establishing his or her exposure status. The objective of this study was to investigate the reliability and feasibility of SAE approaches among shoe repair workers collecting exposure data over a 3 month period. This study was conducted in 26 Dutch shoe repair shops, which were divided into two groups of SAE with different levels of expert supervision. Participants in group 1 received only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Another study showed that in 2004 [28], in a French serigraphy company, the median atmospheric concentration of solvents was 80.1 mg/m 3 for benzoic hydrocarbons. In the Netherlands, Hertsenberg et al [29] found average hexane and toluene concentrations respectively of 25.7 and 26.0 mg/m 3 in shoe repair shops during 2005. Average urinary concentration of 2,5-hexandione was 3.2 ± 2.9 mg/l among shoe makers in Turkey in 1997 [30], and the mean of hexane was 411.6 mg/m 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that in 2004 [28], in a French serigraphy company, the median atmospheric concentration of solvents was 80.1 mg/m 3 for benzoic hydrocarbons. In the Netherlands, Hertsenberg et al [29] found average hexane and toluene concentrations respectively of 25.7 and 26.0 mg/m 3 in shoe repair shops during 2005. Average urinary concentration of 2,5-hexandione was 3.2 ± 2.9 mg/l among shoe makers in Turkey in 1997 [30], and the mean of hexane was 411.6 mg/m 3 .…”
Section: Discussionmentioning
confidence: 99%
“…The example is based upon the study reported in Hertsenberg et al (2007); data from this study are held within the ART database. Contextual information about this AS is provided as supplementary information (available at Annals of Occupational Hygiene online).…”
Section: Worked Examplesmentioning
confidence: 99%
“…In practical use of the ART, a user would have to judge the most appropriate data for their AS based upon the contextual information that supplements each data set. For this example, the three data sets corresponding to the study reported in Hertsenberg et al (2007) were selected. These data sets ‘Spreading of glue <1h, LEV’, ‘Spreading of glue 1–2h, LEV’, and ‘Spreading of glue >2h, LEV’ related to the same study; however, the measurements were partitioned by the exposure duration.…”
Section: Worked Examplesmentioning
confidence: 99%
“…Therefore, efforts were taken to reduce sampling costs, for example, by employing passive, instead of active, sampling [ 5 ]. Another approach to reducing the cost of exposure sampling was introduced by Liljelind and co-authors in the early to mid-2000s [ 6 , 7 , 8 ], and this was later explored by others [ 9 , 10 , 11 ]. The concept of self-assessment of exposure (SAE) implies that workers assess their own exposures, instead of occupational hygienists.…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative self-assessment of inhalation exposure relied mainly on passive sampling of volatile organic compounds (VOCs) and gases. Hertsenberg et al, (2006) reported the results of a quantitative study on VOC exposure amongst shoe repair men, using two different regimes of self-assessment, i.e., different levels of expert supervision [ 9 ]. The group with the lowest level of supervision received only written instructions on the use of the passive samplers (diffusion badges), whereas participants in the other group received extensive oral instructions, followed by controlled assessment of exposure.…”
Section: Introductionmentioning
confidence: 99%